Educação ambiental como instrumento de gestão de recursos hídricos para reduzir os resíduos sólidos no rio Jauaperi, Sul de Roraima - Carvalho, Airlene de Medeiros (2024)
In the riverside region, in Roraima, the scenario has been changing in recent decades. The situation is more critical with the difficulty in accessing basic services, including the distribution of drinking water, sanitary sewage and solid waste collection. These deficiencies place a burden on riverside people, creating a scenario of environmental and social vulnerability. The problems intensify with the increase in consumption of industrialized products and the disposal of solid waste in rivers, mainly a consequence of the lack of alternatives for managing recyclable packaging and a more active non-formal environmental education in traditional communities. In this context, the research was developed in the villages of Itaquera and Xixuaú, bathed by the Jauaperi river, south of the municipality of Rorainópolis, which is part of the last Conservation Unit constituted in the Amazon, called Extractive Reserve (Resex) Baixo rio Branco – Jauaperi, created by Federal Decree nº 9.401/2018.The methodology used in the study was based on technical visits and the socio-environmental questionnaire applied in the two communities with sixteen respondents in total. The exploratory and descriptive research, with a quantitative and qualitative approach, involved online interviews with representatives of riverside families on the Jauaperi River, in order to obtain data on the socioeconomic profile, sanitary conditions and access to health services and education. Environmental problems caused by the irregular disposal of waste on the ground and in the Jauaperi River were identified. It was also verified, through the Roraima epidemiological surveillance report, the notification of water diseases resulting from the consumption of water directly from the river without proper treatment. The lack of non-formal environmental education was evident, as the majority responded that they had not participated in actions that promote environmental education in the communities. Regarding public policies aimed at water resources and solid waste, everyone stated that they were unaware of the subject, making it therefore essential to apply non-formal environmental education to strengthen citizenship. The study served as the basis for the construction of a conceptual and educational environmental manual, to support the management of water resources for the management of solid waste, aiming at water quality in the lower Jauaperi River and promoting the health of the riverside population. Based on the results obtained, it is expected to assist managers and public agents, community leaders and teachers with assertive action planning measures, with the aim of mitigating damage to the extractive population and the Jauaperi river.